Correlates of cigarette and alternative tobacco product use among young tobacco users experiencing homelessness. (August 2019) - Tucker, Joan S.; Shadel, William G.; Golinelli, Daniela; Seelam, Rachana; Siconolfi, Daniel
Abstract: Introduction: Most young people experiencing homelessness smoke cigarettes, but little is known about use of alternative tobacco products (ATPs) such as e-cigarettes or other electronic nicotine delivery systems (ENDS) and little cigars/cigarillos (LCCs). This study examines past month use and correlates of cigarettes and ATP among young tobacco users experiencing homelessness. Methods: We surveyed a probability sample of N = 469 unaccompanied homeless 13–25 year olds (mean age = 22; 71% male), who reported past month use of any type of tobacco product, from 25 service and street sites in Los Angeles County. Results: Nearly all (90%) participants reported smoking regular cigarettes, and 78% reported using at least one tobacco product other than regular cigarettes. The most commonly used of these other products was natural cigarettes (55%), followed by LCCs (43%), ENDS (34%), cigars (31%), hookah (14%), chewing tobacco (7%), and snus (5%). Multivariable models indicated that correlates of past month use differed by product, but included sociodemographic characteristics, homelessness severity, depression, exposure to other people who used the product, and product perceptions (e.g., relative access, cost, and harm compared to cigarettes). Conclusion: Use of cigarettes and ATPs are both widespread among young homeless tobacco users, suggesting that efforts to reduce tobacco use in this population should have a broad focus that includes a variety of products. The effectiveness of these efforts may be enhanced by addressing their considerable exposure to other tobacco users, as well as their perceptions of certain products as being less harmful or more cost-effective options than regular cigarettes. Highlights: Most homeless youth tobacco users smoke cigarettes. Use of alternative tobacco products is widespread as well. Correlates of past month use differ by the type of tobacco product. Exposure to tobacco users and product perceptions may be key intervention targets.